Design and performance of novel self-cleaning g-C3N4/PMMA/PUR membranes - Svoboda, Ladislav; Licciardello, Nadia; Dvorsky, Richard; Bednar, Jiri; Henych, Jiri; Cuniberti, Gianaurelio (Giovanni) (Polymers, 2020)
In the majority of photocatalytic applications, the photocatalyst is dispersed as a suspension of nanoparticles. The suspension provides a higher surface for the photocatalytic reaction in respect to immobilized photocatalysts. However, this implies that recovery of the particles by filtration or centrifugation is needed to collect and regenerate the photocatalyst. This complicates the regeneration process and, at the same time, leads to material loss and potential toxicity. In this work, a new nanofibrous membrane, g-C3N4/PMMA/PUR, was prepared by the fixation of exfoliated g-C3N4 to polyurethane nanofibers using thin layers of poly(methyl methacrylate) (PMMA). The optimal amount of PMMA was determined by measuring the adsorption and photocatalytic properties of g-C3N4/PMMA/PUR membranes (with a different PMMA content) in an aqueous solution of methylene blue. It was found that the prepared membranes were able to effectively adsorb and decompose methylene blue. On top of that, the membranes evinced a self-cleaning behavior, showing no coloration on their surfaces after contact with methylene blue, unlike in the case of unmodified fabric. After further treatment with H2O2, no decrease in photocatalytic activity was observed, indicating that the prepared membrane can also be easily regenerated. This study promises possibilities for the production of photocatalytic membranes and fabrics for both chemical and biological contaminant control.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Exfoliated carbon nitride; Immersion coating; Membrane; Photocatalysis; Poly(methyl methacrylate); Polymers; Polyurethane nanofibers; Self-cleaning surfaces